Bioreductive fluorescent imaging agents: applications to tumour hypoxia. Issue 58 (29th February 2016) - Elmes, Robert B. P.
Abstract : The development of new optical chemosensors for various reductases presents an ideal approach to visualise areas of tissue hypoxia. Abstract : Large tumours contain regions with very low intracellular O2 concentrations. Known as hypoxia, this feature of tumours yields a highly reducing environment owing to the presence of numerous oxygen sensitive reductase enzymes. The development of new optical chemosensors for these various reductases presents an ideal approach to visualise areas of hypoxia or highly reducing environments. Critical to the success of such chemosensors is the design of probes containing a bioreductively activated moiety that either ensures the selective retention of fluorescence within a hypoxic tissue or a probe that irreversibly releases a reporter fluorophore. This Feature Article aims to summarise the fluorescent tools that have been developed to image tumour hypoxia and the various reductase enzymes associated with the bioreduction process.